2017
DOI: 10.1590/1982-0224-20170023
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of environmental factors to fish assemblages in the Río Acahuapa, a small drainage in Central America

Abstract: The ichthyofauna of the Río Acahuapa was analyzed sampling 17 sites that included the basin main channel and its tributaries. Fish were collected using dip-nets, seine-nets and electrofishing. Fish standard length and species abundance were recorded. Species origin and salinity tolerance criteria were used to classify fish species. Water physicochemical variables, habitat structure and sampling sites elevation were recorded. A total of 33 fish species were registered, 12.1% are primary, 45.5% are secondary and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…It is noteworthy that a loading score of 0.30 or above is considered good, 0.40 or above is considered significant and 0.50 or above is considered highly significant (Lomberte et al 2012). In the present study, loading score greater than 0.6 was extracted for each principal component following Alvarez et al (2017) which were statistically significant and indicated closely associated variables with PC1 and PC2. The most significant loadings on PC1 were turbidity, TDS, calcium, magnesium, nitrate and chloride, and those on PC2 were dissolved oxygen and alkalinity.…”
Section: Principal Component Analysismentioning
confidence: 74%
“…It is noteworthy that a loading score of 0.30 or above is considered good, 0.40 or above is considered significant and 0.50 or above is considered highly significant (Lomberte et al 2012). In the present study, loading score greater than 0.6 was extracted for each principal component following Alvarez et al (2017) which were statistically significant and indicated closely associated variables with PC1 and PC2. The most significant loadings on PC1 were turbidity, TDS, calcium, magnesium, nitrate and chloride, and those on PC2 were dissolved oxygen and alkalinity.…”
Section: Principal Component Analysismentioning
confidence: 74%
“…Moreover, PCA was used to determine the components that explained most of the variation and identified water quality parameter measurements that contributed to these variations at the catchments (Achieng et al, 2017). Fish assemblage were analyzed with one-way analysis of similarity (ANOSIM) to inferred significant dissimilarity in fish communities at the catchments, while similarity percentages (SIMPER) was used to separate the fish into relative abundance of specific species that contributed to the dissimilarity at catchments (Álvarez et al, 2017;Achieng et al, 2020;Masese et al, 2020a). Canonical correspondence analysis (CCA) was then used to infer significant relationships between fish species and environmental variables (O'Connell et al, 2004;Hoeinghaus et al, 2007;Junqueira et al, 2016) at the four catchments.…”
Section: Land Use Classification and Statistical Analysismentioning
confidence: 99%
“…In Río Angue, Lontra longicaudis was observed eating an individual of Anableps dowei. Furthermore, fishermen mentioned the occurrence of fishes such as Rhamdia laticauda (Kner, 1858), R. guatemalensis (Gün ther, 1864), Oreochromis niloticus (Linnaeus, 1758), Para chromis motaguensis (Günther, 1867), and Am atitlania nigrofasciata (Günther, 1867), common species and widely distributed in El Salvador (McMahan et al 2013;Álvarez et al 2017;González-Murcia et al 2019), and potential prey species for L. longicaudis in this river. In Río Sapo, Río Negro, and Quebrada de Perquín, feces were found with the presence of fish scales.…”
Section: Discussionmentioning
confidence: 99%